Phosphonium Salts as Pseudohalides: Regioselective Nickel‐Catalyzed Cross‐Coupling of Complex Pyridines and Diazines - Zhang, Xuan; McNally, Andrew (Angewandte Chemie International Edition, 2017)
Heterobiaryls are important pharmacophores that are challenging to prepare by traditional cross‐coupling methods. An alternative approach is presented where pyridines and diazines are converted into heteroaryl phosphonium salts and coupled with aryl boronic acids. Nickel catalysts are unique for selective heteroaryl transfer, and the reaction has a broad substrate scope that includes complex pharmaceuticals. Phosphonium ions also display orthogonal reactivity in cross‐couplings compared to halides, enabling chemoselective palladium‐ and nickel‐catalyzed coupling sequences. Pyridines and diazines can be selectively converted into heterocyclic phosphonium salts that function as generic alternatives to heteroaryl halides in a nickel‐catalyzed Suzuki–Miyaura coupling reaction. Complex pyridines, drug‐like fragments, and pharmaceuticals can be arylated according to this two‐step method.